Eye-Tracking and Pictograms: Improving Communication and Accessibility for Senior Adults - Arias-Flores, Hugo (2024)
An important factor in exploring the world around us and understanding the cognitive process of individuals is analyzing the characteristics and behavior of the eyes, as they provide reliable information. Improving communication processes with users through visual communication environments can create an accessible environment for virtual interaction. In this context, the global population is aging at a faster rate, leading to social transformation. This population segment may face challenges with language skills, health issues, psychological disorders, and traumas that can limit their ability to speak or move. The purpose of this study is to investigate whether eye-tracking, using the eye-tracking device, will enable senior adults to interact with their caregivers through a pictogram-based interface, allowing them to generate messages and communicate their needs. The research method involves the conceptual development of an experiment designed for senior adults, including the use of an eye-tracking device, calibration tests, and interface responses. This research aims to better understand and promote the importance of meeting the needs and expectations of the elderly segment.